FORMULA OF CLASSICAL DETECTIVE IN KNIVES OUT MOVIE DIRECTED BY RIAN JOHNSON - Aidin, Amar Handika; Rasiah, Rasiah; Gultom, Eva Solina (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
This study aims to analyze the formula of classical detective in the Knives Out movie. The problem of this study is what are classical detective formula that appear in Knives Out movie. This study used descriptive qualitative method by using Cawelti’stheory.The data source is taken from the Knives Out movie and analyzed thedata by describing, interpreting, analysis, drawing a conclusion. Based on this analysis, the researcher found out 14 classical detective formula according to Cawelti. This formula includes 11 conventionsas follows: situation, crime and clues, investigation, announcement of the solution, explanation of the solution, denouement, the victims, the criminal, the detective, those threatened by crime but incapable of solving it, setting. In addition, there are 3 inventions found as follows: the victims, the detective, setting and situation. Based on the analysis results, the classical detective formula that appear in Knives Out still maintained the prevaling pattern based on Cawelti’s theory but there are new invention that exist as a response to the development of the classical detective genre from time to time.